Rotavirus Vaccine Virus Shedding, Viremia and Clearance in Infants with Severe Combined Immune Deficiency. Issue 3 (March 2015) - Kaplon, Jérôme; Cros, Guilhem; Ambert-Balay, Katia; Leruez-Ville, Marianne; Chomton, Maryline; Fremy, Céline; Pothier, Pierre; Blanche, Stéphane
Abstract : We report for the first time Rotarix vaccine-acquired rotavirus infections with viremia in 2 infants vaccinated before being diagnosed with severe combined immune deficiency. Monitoring the first infant revealed that persistent rotavirus infection resolved after complete immune reconstitution was achieved by gene therapy. Abstract : Supplemental Digital Content is available in the text.